Integrative systematics untangles the evolutionary history of Stenochrus (Schizomida: Hubbardiidae), a neglected junkyard genus of North American short-tailed whipscorpions. (28th May 2020) - Monjaraz-Ruedas, Rodrigo; Francke, Oscar F; Prendini, Lorenzo
Abstract: Until recently, the Nearctic short-tailed whipscorpion genus, Stenochrus Chamberlin, 1922, included 27 species distributed primarily in Mexico, the USA and Central America. Morphological disparity among its species, associated with their adaptation to diverse habitats, raised the question as to whether Stenochrus was monophyletic. The phylogenetic relationships among short-tailed whipscorpions have only recently begun to be explored, and the monophyly of Stenochrus had never been tested. The present contribution provides the first phylogeny of Stenochrus and related genera, based on 61 morphological characters and 2991 aligned DNA nucleotides from two nuclear and two mitochondrial gene markers, for 73 terminal taxa. Separate and simultaneous analyses of the morphological and molecular data sets were conducted with Bayesian Inference, Maximum Likelihood, and parsimony with equal and implied weighting. Terminals represented only by morphological data ('orphans') were included in some analyses for evaluation of their phylogenetic positions. As previously defined, Stenochrus sensu Reddell & Cokendolpher (1991, 1995 ) was consistently polyphyletic and comprised eight monophyletic clades, justifying its reclassification into eight genera including Heteroschizomus Rowland, 1973, revalidated from synonymy with Stenochrus by Monjaraz-Ruedas et al. (2019) . Rowland & Reddell's (1980) mexicanus and pecki species groups were consistently paraphyletic. Orphans grouped with the most morphologically similar taxa.